Why Do Trump's Authoritarian Followers Resist COVID-19 Authorities? Because They Are Not Really Authoritarian Followers - Hibbing, John R. (Frontiers in Political Science, 2022)
People’s responses to the threat posed by COVID-19 varied widely. In direct contradiction to the popular theory that Trump supporters prefer to submit to powerful people, Trump’s most enthusiastic followers actually were the most vocal in resisting the urgings of authorities to get vaccinated and to wear masks. I explain this anomaly by showing that Trump’s followers are driven less by a desire for authority and more by a desire to be secure from the threats human outsiders pose to society’s historically dominant racial, language, religious, and cultural group. Far from being authoritarians, the followers of leaders such as Donald Trump stridently oppose all authority figures who divert attention from what they believe are the real threats: immigrants, powerful foreign countries, diversity, terrorists, and criminals. From this perspective, it is unsurprising that those with a securitarian orientation would not take seriously authorities who are concerned with the threat posed by an mRNA virus.